Pengalaman Survivor Cancer: Studi Fenomenologi - Distinarista, Hernandia; Anggorowati,; Mardiyono,; Dwidiyanti, Meidiana; Sofro, Muchlis Achsan Udji (Jurnal Keperawatan Soedirman, 2017)
The number of cancer survivors increase in the last decade. The cancer patients' survival rate is 65.8 months and the five-year survival rate is 71.1%. The cancer survivors need information, services, and holistic treatment to have a high quality life. This study aimed to explore cancer survivor experiences of cervical cancer patients.This study used a hermeneutic phenomenological approach, involved five participants in the Central Java Province. The data were collected using semi-structured interview, documented into transcript form then analyzed using content analysis method. The study results revealed that there were five themes: healthy cancer survivor behavior in facing cervical cancer, using complementary or herbal treatment in cervical cancer survivor patient, coping in overcoming problem during cervical cancer treatment, family and health worker support to cervical cancer survivor, spiritual aspect among cervical cancer survivor. Results of this study conclude that the cervix cancer survivors applied several self care methods.